2015
DOI: 10.7314/apjcp.2014.15.23.10225
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Selected XRCC2, XRCC3 and RAD51 Gene Polymorphisms and Primary Breast Cancer in Women in Pakistan

Abstract: Genetic polymorphisms in homologous recombination repair genes cause an abnormal development of cancerous cells. In the present study we evaluated the possibility of breast cancer association with single nucleotide polymorphisms of RAD51, XRCC2 and XRCC3 genes. Polymorphisms selected in this study were RAD51 135G/C, XRCC2 Arg188His; and XRCC3 Thr241Met. Each polymorphism was genotyped using Polymerase chain reaction-restriction fragment length polymorphism in study cohort of 306 females (156 breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…XRCC3 is located in the 14q32.3 chromosome region and plays a key role during HR that is essential for DSB repair and maintaining chromosomal stability . To date, many reports have shown that polymorphisms in the XRCC3 gene are associated with an increased risk for various solid tumors, including breast, bladder and lung cancers . However, the expression profile and clinical significance of XRCC3 protein in cancer remain unknown.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…XRCC3 is located in the 14q32.3 chromosome region and plays a key role during HR that is essential for DSB repair and maintaining chromosomal stability . To date, many reports have shown that polymorphisms in the XRCC3 gene are associated with an increased risk for various solid tumors, including breast, bladder and lung cancers . However, the expression profile and clinical significance of XRCC3 protein in cancer remain unknown.…”
Section: Discussionsupporting
confidence: 89%
“…(17,22) To date, many reports have shown that polymorphisms in the XRCC3 gene are associated with an increased risk for various solid tumors, including breast, bladder and lung cancers. (23)(24)(25) However, the expression profile and clinical significance of XRCC3 protein in cancer remain unknown. To investigate the potential role of XRCC3 in ESCC, we first examined the expression level of XRCC3 protein by IHC in 20 normal esophageal mucosa tissues and 60 ESCC cases with complete follow-up information.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no relationship of rs25489, rs25487 and rs13181 with PTC. The mutations in XRCC genes may cause decrease or loss of DNA repair capacity and confer the variation in development of many malignant tumors, and previously, some studies have reported that XRCC1 and XRCC3 gene polymorphisms may modify the risk for some types of cancer, such as gastric cancer [13], glioma [14], breast cancer [15] and colorectal cancer [16]. But to date, less study focused on the association between XRCC gene polymorphisms and PTC risk, especially for Chinese population, and these published literatures could not concluded a consistent result.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have investigated the association between XRCC3 Thr241Met polymorphism and different types of cancers, but the results are contradictory. Some studies have found that XRCC3 Thr241Met polymorphism is associated with a high risk of cancer, such as glioma, hepatocellular carcinoma, colorectal cancer, breast cancer, head and neck cancer and gastric cancer (Duan et al, 2013;Luo et al, 2013;Kayani et al, 2014;Nissar et al, 2014;Qureshi et al, 2014). Duan and colleagues investigated the role of XRCC3 Thr241Met polymorphism in hepatocellular carcinoma, and reported that the Met/Met and Thr/Met+Met/Met genotypes were significantly associated with hepatocellular carcinoma in a Chinese population (Duan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%